'The Spanish Problem' - TUC report, 1936 (1936)
1936 1918-1939 "'The Spanish Problem' - TUC report, 1936" [T0323.jpg], 1936, Trades Union Congress Report of debates on the Spanish Civil War at the Plymouth Trades Union Congress in 1936.